Ekonomiczne aspekty działalności małych i średnich przedsiębiorstw w agrobiznesie po akcesji z Unią Europejską - Zuzek, Dagmara K. (Economic Aspects of Small and Medium Sized Enterprises Activity in Agribusiness after the Integration with the European Union, 2005)
Small and medium sized enterprises constitute a large and permanent group in the structure of food industry. In certain branches small companies have competitive advantage over large enterprises (bakery, processing of meat, fruits and vegetables). Regarding the above branches small companies show higher profitability of sales, labour efficiency and the efficiency of current asset management then medium and large companies. Proper policy targeted at SME's should take into account two goals: overall conditions of the development of SME's and intervention measures in other sectors and fields of policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 466-472